Answer:
P(B/A)≠P(B)
Step-by-step explanation:
We are given that A and B are two events and P(B/A) is the given probability notation for conditional probability.
For independence of two events with conditional probability the two events are said to be independent if
P(B/A)=P(B)
This equation can be derived from the definition of conditional probability.
P(B/A)=P(A∩B)/P(A)
If two events are independent then P(A∩B)=P(A)*P(B), substituting this in the above equation
P(B/A)=P(A)*P(B)/P(A)
P(B/A)=P(A).
So, if two events are not independent then the notation of probability is
P(B/A)≠P(B)